Anti-GPVI (HY101) activates platelets in a multicolor flow cytometry panel. (3rd October 2022) - van Dievoet, Marie-Astrid; Brusa, Davide; Octave, Marie; Horman, Sandrine; Stephenne, Xavier
Abstract: The platelet transmembrane receptor GPVI can be assessed together with other platelet membrane markers in a whole blood multicolor flow cytometry panel. The advantage of combining multiple antibodies in a single tube is the possibility of distinguishing multiple platelet subgroups. In this short communication, we describe an activation problem encountered with anti-GPVI, clone HY101. Activation of platelets was seen after the addition of anti-GPVI in a flow cytometry panel, highlighted by the expression of the activation markers CD62P, PAC-1, CD63, and CD107a. This was also confirmed by platelet aggregation studies.